Deformation characteristics of an ultra-deep and small-scale rectangular excavation in Hangzhou soft clay. (July 2023) - Liu, Nianwu; Pan, Jingjie; Li, Mingguang; Li, Ying
Highlights: Deformation characteristics of an ultra-deep and small excavation were examined. Owing to the spatial effect, the maximum deformations were comparatively small. Constructions prior to excavation caused 30%–50% of total building settlements. Abstract: A stereogarage excavation was carried out in Hangzhou soft clay. The excavation was approximately 46.2 m deep, 10.8 m wide, and 24.4 m long. The spatial effect of this excavation was expected to be significant because of the minimum aspect ratio of B / H e = 0.23, where B is the excavation width and H e is the final excavation depth. This study examined the deformation characteristics of this ultra-deep and small-scale rectangular excavation through a comprehensive instrumentation program. Analyses of field data indicated that owing to the spatial effect, the maximum wall deformation. δhm and ground settlement δvm were less than 0.2% and 0.04% of the excavation depth, respectively, which were substantially smaller than those of similar excavation projects. For the ultra-deep excavation, the location of the maximum wall deformation was dominated by both excavation depth and stratum distribution. Construction of diaphragm walls and soil improvement prior to excavation caused significant building settlements, which accounted for 30%–50% of the total settlements. This project could serve as a special case study and provide insights into the design and construction of stereogarages in metropolitan environments with soft soil deposits.